ANALISIS KESESUAIAN BIOGEOFISIK PANTAI LABUHAN HAJI SEBAGAI KAWASAN WISATA DI KABUPATEN LOMBOK TIMUR - Hafizin, Hafizin; Putra, Agus Muliadi (Geodika: Jurnal Kajian Ilmu dan Pendidikan Geografi, 2017)
The lack of medium, infrastructure, and information on support authority of tourism area is an inhibitor factor of the tourism development in Labuhan Haji beach. The objective of this research is to analyze the appropriateness of Labuhan Haji to become a tourism area in East Lombok based on the beach bio-geo-physic, depth, the type, the width, the material of bottom waterworks, the current speed, the brightness, dangerous biota, and the fresh water supply. This research is quantitative descriptive. There area 19 station investigated in this research. The data gathered based on the parameter in each station are then analized using Tourism Suitability Index (Indeks Kesesuaian Wisata/IKW) which is agreed with beach tourism suitability matrix. Based on the data gained from each quay, it can be concluded that all the investigated quays area categorized very suitable. This means that Labuhan Haji beach is included an suitable area to be a beach tourism area especially for bathing, swimming, recreation, and enjoying the beauty of the beach.Keywords: suitability, bio-geo-physic, beach tourism